Gambaran Golongan Darah Sistem ABO dan Rhesus Siswa SMA dalam Kegiatan EXPO 2024 - A. Arviani Desianti Nur; Sitti Rahbiah Akram; Ririn Feriana Basri; Dahniar Dahniar; Dirgah Agum Parawansa (SEHATI: Jurnal Kesehatan, 2025)
Blood is classified into four main types: A, B, AB, and O. Besides the ABO system, the Rhesus (Rh) system is also important to identify. Knowing one's blood type is essential, especially for safe and effective blood transfusions. Blood typing ensures compatibility between donors and recipients.This study was conducted at the Sandeq Ballroom, Claro Hotel Makassar, during the Sulawesi Education Techno (EXPO) 2024, held from January 23–25, 2024. The participants were high school students attending the event. A total of 258 students voluntarily participated in blood and Rh typing using a convenience sampling method. Results showed that blood type O was the most dominant, followed by types B, A, and the least common was type AB. This distribution is consistent with the general blood type distribution in Indonesia, where blood type O is the most prevalent. This data can serve as a reference for planning future blood donation drives and increasing awareness about the importance of knowing one's blood type, especially among young people